Colonic Epithelial PHLPP2 Deficiency Promotes Colonic Epithelial Pyroptosis by Activating the NF-κB Signaling Pathway. (6th August 2021) - Li, De-feng; Chang, Xin; Zhao, Jiu-long; Chen, Xuan-min; Xu, Zheng-lei; Zhang, Ding-guo; Wu, Ben-hua; Wang, Li-sheng; Bai, Yu; Yao, Jun
Abstract : Background . Ulcerative colitis (UC) is a chronic inflammatory disease with increasing prevalence worldwide. Barrier defect in intestinal epithelial cells (IECs) is one of the main pathogeneses in UC. Pyroptosis is a programmed lytic cell death and is triggered by inflammatory caspases, while little is known about its role in UC. Methods . Differentially expressed genes (DEGs) were identified by comparing UC patients with healthy controls from the GEO datasets. The candidate genes involved in pyroptosis were obtained, and the underlying molecular mechanism in the progression of UC was explored in vivo and in vitro . Results . Pleckstrin homology domain leucine-rich repeat protein phosphatase 2 (PHLPP2), a protein phosphatase, was downregulated and involved in regulating inflammation-induced IEC pyroptosis by modulating the NF- κ B signaling in UC through bioinformatics analysis. Moreover, we demonstrated that PHLPP2 was downregulated in UC patients and UC mice. Besides, we found that PHLPP2 depletion activated the NF- κ B signaling and increased the expressions of caspase-1 P20, Gasdermin N, IL-18, and IL-1 β contributing to IEC pyroptosis and inflammation in UC mice. Furthermore, we found that PHLPP2 -/- mice developed hypersensitivity to dextran sulfate sodium (DSS) treatment toward colitis showing activated NF- κ B signaling and dramatically induced expressions of caspase-1 P20, Gasdermin N, IL-18, and IL-1 β . Mechanically, this inflammation-induced downregulation of PHLPP2 was alleviated by an NF- κ B signaling inhibitor in intestinal organoids of PHLPP2 -/- mice and fetal colonic cells. Conclusions . PHLPP2 downexpression activated the NF- κ B signaling and promoted the IEC pyroptosis, leading to UC progression. Therefore, PHLPP2 might be an attractive candidate therapeutic target for UC.